DENTAL MORBIDITY AND COMPLIANCE OF FOREIGN STUDENTS - Бублій Т. Д.; Дубова Л. І. (World of Medicine and Biology, 2015)
The problem is a responsible attitude towards their health patients is an important and pressing problem of modern medicine. not enough attention has been paid to this issue, therefore it is necessary to conduct this research. high prevalence of 97±0.8% and intensity of caries registered foreign students, pathology of periodontal tissues every fourth surveyed. 100% foreign students interested in any information on how to keep your teeth healthy. Source of information is a doctor from 76 ± 6.16%. reliable information about the treatment effect on сompliancely behavior of foreigners in 52% of cases, 79± 6.16% perform all doctor's recommendation, a psychological comfort in a relationship with the doctor is leading in 44% of cases.
Keywords: compliance; foreign students; dental status